POSSIBILITIES OF USING THE GAME LEARNING AS A PROCESS OF IMPROVEMENT DIALOGUE COMMUNICATION FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the various problems and aspects of  communicational culture formftijn in dialog training studying situation of professional oriention.